The Improvement of Approaches to Service Activities Teaching - KOZHEVNIKOVA, Margarita Anatolyevna; KUZNETSOVA, Liliya Vasilyevna; SHERMAZANOVA, Svetlana Victorovna; LOPATINSKAYA, Victoria Valerievna; SHELYGOV, Aleksandr Vladimirovich (Journal of Environmental Management and Tourism; Vol 11 No 6 (2020): JEMT Volume XI, Issue 6(46) Fall 2020, 2020)
The article is devoted to the formation of approaches to service activities teaching. The analysis of these approaches has led to the understanding of the new content of services in the tourism and hospitality industry, creating a high-quality infrastructure of innovative business based on service innovations arising as a result of the interaction of innovative stakeholders. It is revealed that the common values of entrepreneurial culture of innovation subjects, providing the possibility of beneficial cooperation and optimal use of common resources, can become the basis for such interaction. It is proved that a special role within the framework of the modern phase of the development of the tourism and hospitality industry should be played by entrepreneurial universities that effectively implement projects of academic and intellectual entrepreneurship and create fractals of entrepreneurial culture. Within the framework of creating a system to ensure the innovative development of the tourism and hospitality industry, they add new functions of the initiator of innovative stakeholders' interaction to their traditional functions of training specialists.